A Journey through the “Contemporary Picturesque” - Marina Tornatora (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
Saint-Non invites scholars to reflect on the meaning of the word picturesque and grasp its deeper significance going beyond the derogatory connotation bestowed on it. The narration is not a mere description of the places visited but rather an aesthetic experience that matches different realities and establishes relationships among differences. The picturesque vision becomes an aesthetic category underlain by composition rules that stem from both visual awareness and imagination which, in particular, makes the vision aesthetically pleasurable allowing to recognize and spot the stylistic elements of a picturesque composition. From this standpoint today, the architectural compositions conceived as a set of relationships perceived by the observer while moving through a space and experiencing a ‘promenade architecturale’ that is not shaped by geometry but rather by the voids defining the parts and volumes that give substance to a setting for a sequence of architectural effects, can be referred to as picturesque. The concept conveyed by the word picturesque switches from the bidimensionality of landscape painting towards the multiplicity of sights and spaces experienced through movement. These considerations open a new perspective for research on the concept of contemporary public open space that can be meant as space for relationships and landscape experiences through movement, knowledge and perception.